Adolescent Mothers' Implementation of Strategies to Enhance Their Children's Early Language and Emergent Literacy Skills. (August 2020) - Towson, Jacqueline; Canty, Meredith; Schwartz, Jamie; Barden, Sejal; Sims, Tianna
Research regarding specific strategies adolescent mothers (AMs) may utilize to facilitate early language and emergent literacy skills in their children is lacking. This exploratory study investigated AMs' perceived use of preselected common language and emergent literacy strategies and correlated their use of these strategies to their children's language skills. In total, 12 AMs enrolled in an alternative school program were surveyed using the Self-Assessment of Language and Literacy Implementation (SALLI) and also completed a self-report of their child's language development using the norm-referenced MacArthur-Bates Communication Development Inventories (CDI). Data were analyzed using descriptive statistics and Spearman's Rank Correlation to determine the significance and relationship between variables. AMs scored low on the SALLI, with the lowest scores specifically in the areas of Directiveness and Home Environment. Results on the CDI indicated that the children had below average receptive and expressive language skills.